REBUSAN LIDAH BUAYA TERHADAP KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELITUS TIPE II - Syapitri, Henny; Marbun, Agnes Silvina; Siregar, Laura Mariati; Efrina Sinurat, Lasma Rina; Berampu, Rani Mukherzi (Jurnal Online Keperawatan Indonesia, 2024)
Diabetes Mellitus (DM) is a chronic condition characterized by a chronic increase in blood glucose concentration accompanied by various metabolic abnormalities due to hormonal disorders, which causes various chronic complications. Diabetes mellitus is caused by the pancreas failing to produce insulin or insulin resistance occurs. Based on data from the World Health Organization (WHO), DM is a serious threat to human health in the 21st century. The number of DM sufferers reached 422 million people in the world in 2018. Most of these sufferers are in developing countries. This type of research uses a pre-experiment using a one group pretest-posttest design.  This study only used one intervention group and there was no comparison (control) group. This research was used to see the effect of giving boiled aloe vera water on blood sugar levels before and after the intervention. The population of this study was all 76 Type II Diabetes Mellitus sufferers who came for treatment at the Pratama Ridho Clinic from January 2024 to July 2024. The sample for this research consisted of 43 respondents. The research method used was the wilcoxon test with a p value (0.05). The research results showed that there was an effect after giving aloe vera decoction at the Pratama Ridho Clinic in 2024 with a value of 0.016.